Application Security Testing to Support Digital-Based Cultural Ecosystem in Jogja Smart Province - Sahirul Alam; Sri Lestari; Budi Bayu Murti; Nur Rohman Rosyid; Ronald Adrian; Anni Karimatul Fauziyyah; Muhammad Hamdan; Josua Rusdi Hutagaol; Sakhiya Abida; Ingrid Rorez Dialusi Sinurat (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
The Jogja Smart Province (JSP) is a framework for using IT to encourage regional cooperation to assist in resolving specific strategic challenges or difficulties. Additionally, JSP supports the growth of potential in Yogyakarta’s Special Region. Several digital apps, including mobile and web-based ones, support JSP. These applications are crucial to actualizing the five JSP aspects of smart living, culture, society, environment, and governance. However, several significant issues, such as cyberattacks on JSP applications, pose a danger to the long-term viability of JSP. To do penetration testing of JSP-owned applications, the Department of Electrical Engineering and Informatics at the Vocational College of Universitas Gadjah Mada is conducting this community participation initiative. The Communication and Informatics Office of the Special Region of Yogyakarta permitted to handle JSP apps, is a partner in this community involvement initiative. Applications including Jogja Istimewa, Visiting Jogja, e-Prima, BiroHukum, Paperless, Jogjaplan, LPSE, Peladen, Sadewa, Jogjaprov, and Simpeg2 are among those targeted for penetration testing. The potential flaws detected in JSP applications can be found by performing penetration testing on these apps. In addition, several recommendations are made to strengthen JSP applications’ resistance to future cyberattacks. Therefore, this activity can improve the security of the users’ data and directly impact the community.